Love me [videorecording (DVD)] - Spesyvt͡seva, Viktorii͡a, 1973-; Cakir, Ushan (Film Movement series., 2015)
Sasha is an attractive young Ukrainian woman who finally decides to end her dead-end relationship with a married man. Cemal, bound by tradition to marry a girl he's never met, is dragged by his uncle and cousin from Turkey to Kiev for a bachelor party. When their paths cross at a nightclub, everything changes for these two lost souls.